Types of written feedback on ESL student writers' academic essays and their perceived usefulness - Tee, Pei Leng (2011)
Feedback is essential for the development of a student writer in an academic context. The feedback that lecturers provide on students’ writing is essential to encourage and develop students’ writing. However, there are limited studies which look at feedback as a form of communication. This study investigates the types of written feedback that lecturers provide to their students. The written feedback was analysed using a speech act theoretical model in order to understand how feedback acts as a communicative act between the lecturer and student writers. The data employed in this study were students’ written drafts, uestionnaires, and interviews with the students and the lecturers. Looking at how language is used in its situational context, the feedback was coded and a model for analysis was developed based on two aspects of speech acts which are directive and expressive. Based on this analysis, the study discusses the types of feedback that the writers found useful in their essay revision. The results indicate that directive and expressive feedback were the most favoured type of feedback among the student writers as the related lecturer comments were clear, direct, and information loaded. A second finding is that the student writers valued content feedback more compared to surface level feedback because it helped them understand their strengths and weaknesses and it provided them clear directions on how to improve their writing. The study concluded that it is important for lecturers to be aware of the impact of feedback and the types of feedback they provide to their students. The study also suggests a possibility of developing a taxonomy of good feedback practices for teachers/lecturers.